Trend analysis of teenage pregnancy in Nigeria (1961-2013): how effective is the contraceptive use campaign - Adeniyi Francis Fagbamigbe; Rotimi F. Afolabi; Oyindamola B. Yusuf (International Journal of Public Health Science (IJPHS), 2019)
Teenage pregnancy (TP) is a recurrent global and public health problem. It poses both social and health challenges. Considering the massive campaign on the use of modern contraceptives to prevent TP in recent decades, we assessed trends in TP in Nigeria between 1961 and 2013. Pregnancy and contraception history of 70,811 women who were at least 20 years old when the Nigerian DHS was conducted in 1990, 2003, 2008, and 2013 respectively were used for the study, and descriptive statistics, time analysis techniques and multiple logistic regression were used to analyze the data at 5% significance level. The overall prevalence of TP between 1961 and 2013 was 49.5% which fluctuated insignificantly during the studied period. The TP prevalence among women who entered adulthood in 1961 was 39.2%; it peaked in 1978 at 58.9% before its unsteady decline to 39.6% in 2012, and then rose sharply to 55.6% in 2013. We predicted TP prevalence as 49.0%, 49.9% and 51.0% in 2014, 2015 and 2016 respectively. The odds of TP were over 4 times higher in the North East and 5 times higher in the North West than in the South West. Teenagers with no education had higher odds of TP and it was higher among teenagers from the poorest households (OR=5.64, 95% CI: 5.36-5.94). Rather than reducing with the worldwide acknowledged increase in contraceptive campaigns, TP increased over the years studied. As far as TP is concerned in Nigeria, the impact of the campaign on MC use is far from being effective. To achieve the objective of fewer TPs, fewer resources should be spent on access to contraception and instead diverted to areas more likely to achieve results such as improvements in educational achievement amongst girls.